Case of Ovarian Hyperstimulation Syndrome with Ovarian Torsion: An Unusual Complication of Primary Untreated Hypothyroidism - Gwendolyn Fernandes; Manali Patil; Caroline Thomson (Journal of Clinical and Diagnostic Research)
Ovarian Hyperstimulation Syndrome (OHSS) is an extremely unusual complication of ovarian induction therapy given for infertility. OHSS can also occur spontaneously in ovulation cycles linked to polycystic ovarian disease, multiple gestations, molar pregnancy, pituitary adenomas and very rarely, hypothyroidism. It can result in significant morbidity and mortality in severe forms due to thrombosis and organ failure. A 28-year-old non pregnant woman presented to the emergency services with severe abdominal pain associated with nausea, vomiting, constipation and burning micturition. The symptoms began four to five days ago and the pain, which was initially localised to the left iliac fossa, progressed to involve the entire abdomen. Ultrasonography revealed large, bulky, oedematous ovaries with multiple cysts of varying sizes, indicative of OHSS, along with torsion of the left ovary. There was no history of receiving beta-human Chorionic Gonadotropin (β-hCG), clomiphene citrate, estradiol, oral contraceptive pills, or any other ovulation induction therapy. A salpingo oophorectomy was done for the left ovary and cystectomy with ovarian reconstruction was done for the right ovary. Histopatholgical examination confirmed OHSS (Type 3) with ovarian torsion. The patient had a diagnosis of primary hypothyroidism during pregnancy which was three and half years ago and was treated with Thyroxine 75 μg per day. However, stopped thyroxine on her own immediately after delivery. Thyroid Stimulating Hormone (TSH) levels was 110 μg, T3 was 16 ng/mL and T4 was 0.91 μg/dL. Thyroxine 100 μg/day was started and the contralateral ovary returned to the normal size on ultrasonography within a period of three months. Thus, OHSS resulted from primary hypothyroidism and was cured with thyroid hormone replacement. OHSS may also be considered in the differential diagnosis in patients of hypothyroidism patients presenting with abdominal symptoms.